Age and memory related changes in children's immediate and delayed suggestibility using the Gudjonsson Suggestibility Scale. (November 2016) - Gudjonsson, Gisli; Vagni, Monia; Maiorano, Tiziana; Pajardi, Daniela
Abstract: The main aim of this study was to investigate age, gender and memory effects on 'immediate' and 'delayed' suggestibility among children, and the relationship between immediate and delayed suggestibility. The participants were 1183 children aged between 7 and 16 years, who had been divided into three age band groups (7–9, 10–12, and 13–16 years). All children completed the Gudjonsson Suggestibility Scale (GSS 2) and a non-verbal IQ test. Delayed suggestibility was measured after a one week delay. There were significant memory and suggestibility effects across the three age groups. Girls had significantly higher immediate and delayed memory scores than boys, but did not differ on suggestibility. Suggestibility predicted age after controlling for immediate recall, indicating significant incremental effects. Immediate and delayed suggestibility were significantly correlated in the two older age groups, but the effect sizes were small. The results suggest that immediate and delayed suggestibility are poorly correlated, and the effects of age and immediate recall are largely confined to immediate suggestibility, indicating that immediate and delayed suggestibility are underpinned by different processes. What they have in common is poor source monitoring (discrepancy detection), but differ in terms of how the interviewee processes the flawed source monitoring over time. Highlights: Immediate suggestibility is related to age and memory. Delayed suggestibility is not related to age. Age predicted immediate suggestibility beyond memory. Immediate and delayed suggestibility are poorly related.